2006
DOI: 10.1128/jvi.00945-06
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Horsepox Virus

Abstract: The genus Orthopoxvirus includes members of the family Poxviridae historically relevant to human health-variola virus (VARV), the etiologic agent of smallpox, and vaccinia virus (VACV), the vaccine virus used to eradicate smallpox (32). Other orthopoxviruses (OPVs), similar to VACV, are zoonotic and significant for human health, including monkeypox virus (MPXV) and cowpox virus (CPXV) (33). Still others, similar to VARV, remain restricted to specific, albeit nonhuman, hosts, including camelpox virus (CMLV) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 90 publications
2
117
0
2
Order By: Relevance
“…Curiously, the virus that was eventually used to eradicate smallpox was one now called vaccinia virus (VACV), another orthopoxvirus but one that is clearly different from any known strain of CPXV. The biological origin of VACV is uncertain, although it has been suggested that a horsepox-like virus was an ancestor, even though a surviving horsepox virus (HPXV) ge-nome harbors many extra genes (8). This hypothesis is supported by Jenner's report that he obtained his later inocula from an infection in horses called "grease" (5).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Curiously, the virus that was eventually used to eradicate smallpox was one now called vaccinia virus (VACV), another orthopoxvirus but one that is clearly different from any known strain of CPXV. The biological origin of VACV is uncertain, although it has been suggested that a horsepox-like virus was an ancestor, even though a surviving horsepox virus (HPXV) ge-nome harbors many extra genes (8). This hypothesis is supported by Jenner's report that he obtained his later inocula from an infection in horses called "grease" (5).…”
supporting
confidence: 62%
“…DNA containing DVX_010 to DVX_013 replaces sequences in this gap and is present in both VACV TIRs, while HPXV/CPXV retains these sequences only at the right end of the genome. It has been suggested that the VACV telomeres were created by a transposition of these sequences from the right to the left end of an HPXV-like genome (8). However, since the HPXV TIR still harbors homologs of the genes DVX_001 to DVX_009, it is more likely that the entire region (from DVX_013 to DVX_001 and corresponding to HPXV_196 to the end of the HPXV genome) transposed from the right to the left end of this hypothetical common ancestor.…”
Section: Dpp25 Sequencing and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation is that VV originates from a virus that lacks the ability to retain MHC class I. Although the origin of VV is not entirely clear, recent evidence suggests that VV is much more closely related to horsepox virus (HSPV) than to either CPV or MPV (39). Moreover, experimental infection of horses with VV can produce the same clinical symptoms as those of HSPV (40).…”
Section: Discussionmentioning
confidence: 99%
“…During the years of vaccination, the use of the live vaccine virus we now call vaccinia virus replaced the original cowpox virus, but the exact period in history that the change occurred is unknown. Today we know that vaccinia virus is genetically and biologically distinct from the poxviruses that we now call cowpox and horsepox viruses [21].…”
mentioning
confidence: 99%